Forage yield and nutritive value of hay from sorghum-sudangrass hybrids (Research, Society and Development, 2020)
The objective was to evaluate agronomically nine sorghum-sudangrass hybrids (Sorghum bicolor × Sorghum sudanense) and the nutritive value of their respective hays. The experimental design used was randomized blocks in a 3 × 9 factorial scheme, with three replications. Three cuts were made: 42 days after germination, 29 days after regrowth, and 28 days after the second regrowth. All hybrids showed a higher number of plants ha–1 (P  0.05) in dry matter, mineral matter, or ether extract. The hybrids 1013020, BRS 810, 1013016, and 1624F016 showed higher values of crude protein (CP) of 16.49, 16.17, 16.08, and 15.88%, respectively. Differences were observed (P 13% and NDF content